Collection of X-ray micro computed tomography images of shells of planktic foraminifera with curated taxonomy - Siccha, Michael; Morard, Raphael; Meilland, Julie; Iwasaki, Shinya; Kucera, Michal; Kimoto, Katsunori (PANGAEA, 2023)
Calcite shells of planktic foraminifera (Protista, Rhizaria) constitute a large portion of deep-sea sediments. The shells are constructed by sequential addition of partly overlapping chambers with various shapes, resulting in complex shell architectures, which are genetically fixed and diagnostic at the species level. The characterisation of the architecture requires three-dimensional imaging of the shell, including the partially or entirely covered juvenile chambers. Here we provide reconstructed x-ray micro computed tomography image stacks of 179 specimens of extant planktic foraminifera collected from plankton tows, sediment traps and surface sediments. The specimens have fully resolved and curated taxonomy and represent 43 of the currently recognised 48 holoplanktic species and subspecies. The image stacks form a basis for further applications, such as the characterisation of the architectural morphospace of the extant taxa, allowing studies of species functional ecology, calcification intensity and reconstructions of phylogenetic relationships.
Keywords: morphology; Morphometry; planktic foraminifera; X-ray micro-CT